A mixed turbidite – contourite system related to a major submarine canyon: The Marquês de Pombal Drift (south‐west Iberian margin). Issue 5 (19th March 2021) - Mencaroni, Davide; Urgeles, Roger; Camerlenghi, Angelo; Llopart, Jaume; Ford, Jonathan; Sanchez Serra, Cristina; Meservy, William; GrÀcia, EulÀlia; Rebesco, Michele; Zitellini, Nevio
Abstract: Synchronous interaction between bottom currents and turbidity currents has been reported often in channel–levée systems where the thickness of the turbidity currents exceeds that of the levées. Such interplay between along‐slope and down‐slope sedimentary processes is one of the mechanisms by which 'mixed turbidite–contourite systems' can originate. However, bottom currents flow over large areas of the seafloor, including continental slopes characterized by deeply incised submarine canyons rather than channel levées. In these cases, a direct interaction between along‐slope and down‐slope currents is, theoretically, unlikely to take place. In this study, oceanographic, swath bathymetry, multichannel seismic data and sediment cores are used to investigate a 25 km long, 10 km wide and up to 0.5 km thick deep‐sea late Quaternary deposit that sits adjacent to the north‐west flank of one of the major canyons in the North Atlantic, the São Vicente Canyon, in the Alentejo Basin (south‐west Iberian margin). The area receives the influence of a strong bottom current, the Mediterranean Outflow Water, which has swept the continental slope at different water depth ranges during glacial and interglacial periods. Architectural patterns and sediment characteristics suggest that this sedimentary body, named Marquês de Pombal Drift, is the result of the interaction between the Mediterranean Outflow Water (particularly during cold periods) and turbidity currents flowing along the São Vicente Canyon. Because the canyon is incised significantly deeper ( ca 1.5 km) than the thickness of turbidity currents, an additional process, in comparison to earlier models, is needed to allow the interaction with the Mediterranean Outflow Water and transport sediment out of the canyon. In the São Vicente Canyon, and likely in other canyons worldwide, interaction of turbidity currents with contour currents requires intermediate nepheloid layers that export the finer‐grained fraction of turbidity currents out of the canyon at the boundary between major water masses.